Pharmacokinetic-Interactions of BI 425809, a Novel Glycine Transporter 1 Inhibitor, with Cytochrome P450 and P-Glycoprotein Substrates: Findings from in Vitro Analyses and an Open-Label, Single-Sequence Phase i Study - Desch, Michael; Schlecker, Christina; Hohl, Kathrin; Liesenfeld, Karl Heinz; Chan, Tom; Müller, Fabian; Wunderlich, Glen; Keller, Sascha; Ishiguro, Naoki; Wind, Sven (Journal of Clinical Psychopharmacology, 2023)
Purpose/Background Glycine transporter-1 inhibitors may ameliorate cognitive deficits in schizophrenia. This study evaluated potential drug-drug interactions with the glycine transporter-1 inhibitor BI 425809. Methods/Procedures Interactions with cytochromes P450 (CYP) and P-glycoprotein (P-gp) were assessed in in vitro assays using human hepatocytes and Caco-2 cells, respectively. Pharmacokinetic characteristics of probe drugs were subsequently assessed in a Phase I, open-label, single-sequence crossover study in healthy male participants. Participants received a probe-drug cocktail containing midazolam (CYP3A4), warfarin (CYP2C9), and omeprazole (CYP2C19) and a separate dose of digoxin (P-gp), alone and on a background of steady-state BI 425809 25 mg once daily in 2 treatment periods. Adverse events were monitored. Findings/Results In vitro assays revealed concentration-dependent induction of CYP3A4 and inhibition of P-gp by BI 425809. In the clinical study, 12 of 13 participants completed both periods. With BI 425809, area under the plasma concentration curve from administration to the last measurement (AUC0-tz) and maximum plasma concentration (Cmax) for midazolam were lower than when administered alone. Adjusted geometric mean ratios (90% confidence interval) were 70.6% (63.9%-78.1%) for AUC0-tz and 77.6% (67.3%-89.4%) for Cmax. For warfarin and digoxin, AUC0-tz and Cmax were similar with and without BI 425809. For omeprazole, BI 425809 slightly reduced AUC0-tz but not Cmax versus omeprazole alone. No new safety signals were identified. Implications/Conclusions These findings indicate induction of CYP3A4 by once-daily BI 425809 25 mg (the assumed highest therapeutic dose) and no meaningful effects on CYP2C9, CYP2C19, or P-gp in vivo.
CRIS-Team Scopus Importer:2023-03-17
Keywords: BI 425809; CYP3A4; drug-drug interaction; glycine transporter-1 inhibitor